Expressão de matriz metaloproteinases e PCNA me úlceras corneais profundas, induzidas em coelhos, tratadas com plasma rico em plaquetas - Perches, Cintia Sesso [UNESP] (2014)
The aim of this study was to evaluate the influence of platelet-rich (PRP) and poor (PPP) plasma in cell proliferation and matrix metalloproteinases (MMPs) expression during the repair of deep corneal ulcers. Forty-five female rabbits were distributed in 3 experimental groups (G) (n = 15), referred as PRP (GR), PPP (GP) and Control groups (GC), in accordance with the treatment. All animals underwent surgical induction of unilateral corneal ulcer. PRP and PPP eyedrops were made by using centrifuged blood through standardized protocol, and instilled five times a day. In GC, lubricant eyedrops was used. Each group was subdivided (n = 5), according to the final time point, 4 (M4), 7 (M7) and 30 days (M30). The animals corneas were processed for morphological and immunohistochemical analysis for PCNA, MMP1, MMP2, MMP9, MT1-MMP and TIMP1. In M4, the levels of MMP2 were higher in GP and GR, and in M7, this behavior was only observed in the GP. In M30, more epithelial cells and MMP1 expression were found in GR than GP. In the GR, cell proliferation was higher in M4 than at others time points and MMP2 expression was higher in M4 than in M30. The PRP stimulates cell proliferation in the early phase (M4) of treatment when compared to other time points, different from other treatments. The use of platelet-rich and poor plasma eyedrops influences the expression of matrix metalloproteinases involved in the corneal repair process